Interaction of Manganese-Doped Copper Oxide Nano-Platelets with Cells: Biocompatibility and Anticancer Activity Assessment - Ioan-Ovidiu Pană; Alexandra Ciorîță; Sanda Boca; Simona Guțoiu; Irina Kacso; Maria Olimpia Miclăuș; Oana Grad; Ana Maria Raluca Gherman; Cristian Leostean; Maria Suciu (Biomimetics)
Understanding cellular interaction with nanomaterials represents a subject of great interest for the validation of new diagnostic and therapeutic tools. A full characterization of a designed product includes the evaluation of its impact on specific biological systems, including the study of cell behavior as a response to that particular interaction. Copper and copper-based nanoparticles (CuO NPs) have emerged as valuable building blocks for various biomedical applications such as antibacterial and disinfecting agents for infectious diseases, and the evaluation of the metabolism of food, including the iron required for proteins and enzymes or as drug delivery systems in cancer therapy. In this study, the biological impact of manganese-doped crystalline copper oxide (CuO:Mn) nano-platelets on human normal BJ fibroblasts and human A375 skin melanoma was assessed. The particles were synthesized at room temperature via the hydrothermal method. A complete physicochemical characterization of the materials was performed by employing various techniques including X-ray diffraction, electron microscopy, X-Ray photoelectron spectroscopy, and dynamic light scattering. Morphological investigations revealed a flat structure with nearly straight edges, with sizes spanning in the nanometer range. XRD analysis confirmed the formation of the CuO phase with good crystallinity, while XPS provided insights into the Mn doping. The findings indicate that nano-platelets interact with cells actively by mediating essential molecular processes. The exogenous manganese triggers increased MnSOD production in mitochondria, compensating ROS produced by external stress factors (Cu2+ ions), and mimics the endogenous SODs production, which compensates internal ROS production as it normally results from cell biochemistry. The effect is differentiated in normal cells compared to malignant cells and deserves investigation.